Dynamic sensations of fresh and roasted salmon (Salmo salar) during chewing. (30th January 2022) - Dong, Meng; Zhang, Yu-Ying; Huang, Xu-Hui; Xin, Ran; Dong, Xiu-Ping; Konno, Kunihiko; Zhu, Bei-Wei; Fisk, Ian; Qin, Lei
Highlights: Evaluating the dynamic sensations of salmon during the chewing process. Quantifing free amino acids and 5′-nucleotides released in saliva during chewing. Glutamic acid and IMP released in saliva may induce the umami perception. Glycine and alanine may contribute to sweetness of slamon. Time dimension of tastants released in saliva affect the dynamic sensation of food. Abstract: The sensory perception of food is a dynamic procedure, which is closely related to the released flavor stimuli. Thus, we evaluated the dynamic sensations of fresh and roasted salmon during the chewing process and investigated the tastants released in saliva. For fresh salmon, the fishy, umami, salty, and sweet attributes were perceived successively. Meanwhile, the smoky and fried flavors were the most dominant attributes of roasted salmon at the beginning, then various attributes were perceived. During the chewing process, free amino acids and 5′-nucleotides released in saliva were quantified. Compared to the sensory data, the results demonstrated that glutamic acid and inosine 5′-monophosphate released in saliva might induce the umami perception. The sweet-tasting amino acids alanine and glycine may contribute to sweetness. Therefore, we suggested that the time dimension of tastants dissolved in saliva would affect the dynamic sensation of food, even for complex food materials.